How excessive smartphone and internet use affects sleep in children and young adults - Giedzicz, Katarzyna; Ziemba, Michał; Okońska, Aleksandra; Kozakiewicz, Julia; Moś, Michał; Ziemba, Anna (Quality in Sport, 2025)
Introduction and purpose: In recent years, smartphones and the Internet have significantly affected the daily lives of children, teenagers, and young adults. However, excessive use of smartphones, especially before bedtime, has serious health consequences. The purpose of this study is to review recent research regarding the impact of excessive smartphone use by children and young adults on their sleep (including the ability to fall asleep, total sleep time, and overall sleep quality), systematize existing knowledge, and provide recommendations for sleep hygiene. State of knowledge: Studies show that children and adolescents who spend a lot of time using mobile devices experience difficulty falling asleep, shortened sleep duration, and reduced sleep quality. These sleep problems can lead to serious health consequences, such as depression, anxiety, concentration problems, poor mood, and chronic fatigue. Using mobile devices before bed also affects the psychological processes involved in falling asleep. Activities such as browsing social media, reading the news, or playing games can increase levels of alertness and arousal, making it difficult to enter the relaxed state necessary for falling asleep. Additionally, content absorbed before bedtime can heighten stress and anxiety levels, further reducing sleep quality.